Stones in the Forgotten Sinuses: A Case of Massive Sinomaxilar Rhinolithiasis in a 70-Year-Old Woman with Fibroma-Resembling Manifestations - Oke Kadarullah; Mohammad Nurrizki Haitamy (Lembaga Publikasi Ilmiah Nusantara, 2026)
Rhinolithiasis is a rare condition caused by progressive mineral deposition around retained secretions or foreign material within the nasal cavity. Diagnosis may be challenging because its clinical and radiological manifestations can resemble other chronic sinonasal diseases. We report a case of a 70-year-old woman who presented with progressive left-sided nasal obstruction, foul-smelling nasal discharge, headache, and mild epistaxis for six months. Computed tomography revealed a heterogeneous calcified mass involving the left maxillary sinus and nasal cavity, initially suspected as a sinonasal fibroma. Functional endoscopic sinus surgery was performed, and intraoperative findings demonstrated a large rhinolith occupying the maxillary sinus, middle meatus, and nasal cavity. Complete removal of the lesion resulted in symptom resolution and a favorable early postoperative recovery. This case highlights that massive sinonasal rhinolithiasis can mimic benign sinonasal tumors on imaging. Careful endoscopic evaluation and surgical exploration are essential for establishing the diagnosis and providing definitive treatment.